Regional Autonomy Policy and Its Implications for Social Welfare: A Case Study in the Talaud Islands - Frisca, Susan (International Journal Labs, 2025)
Regional autonomy policies in Indonesia have become one of the main pillars in efforts to improve social welfare, especially in remote areas such as the Talaud Islands. This study aims to analyze the impact of regional autonomy policies on social welfare in the Talaud Islands, taking into account economic, educational, health, and infrastructure aspects. Using a qualitative and quantitative approach, this study collects data from the Central Statistics Agency (BPS) and other relevant sources to provide a comprehensive overview of the socio-economic conditions in the region. The research findings indicate that while regional autonomy offers opportunities for improved well-being, significant challenges remain that need to be addressed to ensure that its benefits are fully realized by the community.